PENGEMBANGAN MODUL FISIKA BERBASIS CTL UNTUK MEMBERDAYAKAN PENGETAHUAN DAN NILAI KARAKTER SISWA - Zaidah, Alpi; Hardani, Hardani; Hidayatulloh, Alpiana (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2020)
This study aimed to: (1) describe the characteristics of the Physics module based on Contextual Teaching and Learning (CTL); (2) knowing the feasibility of a Contextual Teaching and Learning (CTL) based physics module; (3) knowing the use of Physics modules based on Contextual Teaching and Learning (CTL) can empower students’ knowledge and character values. This research method is R&D by referring to the 4-D model (four D model) proposed by Thiagarajan (1974). The 4-D model consists of defining, designing, developing, and disseminating. Modules are assessed based on the feasibility of the material, media, and language, as well as trials (limited and extensive) to students, and the stages of dissemination at the MGMP forum. Research data collection was using questionnaires and needs analysis interview guidelines, validation sheets, response questionnaires, character value questionnaires, character value observation sheets, and disseminate questionnaires. The results of the study were as follows: (1) produce a module based on Contextual Teaching and Learning (CTL). (2) the module is categorized as feasible based on (material expert, media expert, linguist, teacher, colleague) which shows an average value of 86.0> minimum value of eligibility 84.3. This result also supported by good responses from students and the results of dissemination conducted on the MGMP forum which categorizes the modules well. (3) the use of modules can empower students’ character values ​​and knowledge. This is indicated by the results of the character values ​​and knowledge of students> 75% can reach more than KKM.